Investment, Deposit Interest Rates, and Real Sector Performance: A Case Study of Islamic Finance in Malaysia - Regina Niken Wilantari; Eny Lestari Widarni; Suryaning Bawono (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2021)
This study aims to examine the influence of interest rates, GDP, consumption, and investment on Islamic finance in Malaysia. Also, it focuses on the causal relationship between the macroeconomic and humanistic approach in understanding the role of Muslim economics. Data were analyzed using the Vector Error Correction Model and the results showed that interest rates negatively affect the real sector. Therefore, the Islamic financial system with a zero or no interest-based interest rate tends to promote a social economy